2019
DOI: 10.3390/cancers11121903
|View full text |Cite
|
Sign up to set email alerts
|

WISP-1 Promotes Epithelial-Mesenchymal Transition in Oral Squamous Cell Carcinoma Cells via the miR-153-3p/Snail Axis

Abstract: Around half of all patients with oral squamous cell carcinoma (OSCC) present with lymphatic metastasis, a strong predictor of poor survival. Improving survival rates depends on preventing the first step in the “invasion-metastasis cascade,” epithelial-to-mesenchymal transition (EMT), and developing antilymphangiogenesis therapies that antagonize lymphatic metastasis. The extracellular matrix-related protein WISP-1 (WNT1-inducible signaling pathway protein-1) stimulates bone remodeling and tumor progression. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…In addition, HNRNPC also promoted cell proliferation and inhibited apoptosis by bounding to primary miR-21 (pri-miR-21) directly and promoted miR-21 expression in glioblastoma [22]. Increasing number of studies demonstrated that EMT was markedly relevant to OSCC progression [23][24][25]. In our study, expression of N-cadherin, MMP9, Vimentin were up-regulated and E-cadherin was down-regulated after overexpression of HNRNPC.…”
Section: Agingmentioning
confidence: 49%
“…In addition, HNRNPC also promoted cell proliferation and inhibited apoptosis by bounding to primary miR-21 (pri-miR-21) directly and promoted miR-21 expression in glioblastoma [22]. Increasing number of studies demonstrated that EMT was markedly relevant to OSCC progression [23][24][25]. In our study, expression of N-cadherin, MMP9, Vimentin were up-regulated and E-cadherin was down-regulated after overexpression of HNRNPC.…”
Section: Agingmentioning
confidence: 49%
“…Our findings are just one example of how the matricellular protein WISP1 alters cellular fate and differentiation decisions. Past studies have implicated WISP1 in the balance of osteoblast versus adipocyte formation (38,39) and, more broadly, epithelial cells adopting a mesenchymal cell fate (epithelial-mesenchymal transition) (40)(41)(42)(43). As CCN family members, including WISP1, have numerous extracellular binding partners it is understandable that they may have context-dependent effects on cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…As per previous studies, CCBE1 is indispensable for the development of lymphatic vessels which have important roles in lymphangiogenesis and cancer metastasis [ 30 ]. Tumor lymphangiogenesis plays an important role in LNM of OSCC [ 31 33 ]. Hogan et al suggested that CCBE1 may be an extracellular guidance molecule and an independent factor for normal lymphoblasts to germinate or even migrate [ 34 ].…”
Section: Discussionmentioning
confidence: 99%